A efetividade do conteúdo normativo do artigo 170, da Constituição Federal, na sociedade de consumo - Pintarelli, Camila Kühl (2013)
With this work, we intend to elaborate an analysis about the effectiveness crisis that the precept of the article 170, of Brazilian Federal Constitution, has been showing in the consumption society, especially as a result of the peculiar economic power manifestation in this economic society, in order to, by the end, we demonstrate de importance of insert, in this reality, the fraternity as external element to the normative system, able to reflect in the value complex existent in the social communication of this society, and, consequently, act directly in the migration of those normative precepts from the deontic plan to reality. For that, we will develop our study in four chapters, broaching about fundamental juridical notions, economic order and human rights evolution, economic power and consumption society, and, by the end, fraternity